UDP-glucose Dehydrogenase Polymorphisms from Patients with Congenital Heart Valve Defects Disrupt Enzyme Stability and Quaternary Assembly - Hyde, Annastasia S. (American Society for Biochemistry and Molecular Biology, 2012)
Cardiac valve defects are a common congenital heart malformation and a significant clinical problem. Defining molecular factors in cardiac valve development has facilitated identification of underlying causes of valve malformation. Gene disruption in zebrafish revealed a critical role for UDP-glucose dehydrogenase (UGDH) in valve development, so this gene was screened for polymorphisms in a patient population suffering from cardiac valve defects. Two genetic substitutions were identified and predicted to encode missense mutations of arginine 141 to cysteine and glutamate 416 to aspartate, respectively. Using a zebrafish model of defective heart valve formation caused by morpholino oligonucleotide knockdown of UGDH, transcripts encoding the UGDH R141C or E416D mutant enzymes were unable to restore cardiac valve formation and could only partially rescue cardiac edema. Characterization of the mutant recombinant enzymes purified from Escherichia coli revealed modest alterations in the enzymatic activity of the mutants and a significant reduction in the half-life of enzyme activity at 37 °C. This reduction in activity could be propagated to the wild-type enzyme in a 1:1 mixed reaction. Furthermore, the quaternary structure of both mutants, normally hexameric, was destabilized to favor the dimeric species, and the intrinsic thermal stability of the R141C mutant was highly compromised. The results are consistent with the reduced function of both missense mutations significantly reducing the ability of UGDH to provide precursors for cardiac cushion formation, which is essential to subsequent valve formation. The identification of these polymorphisms in patient populations will help identify families genetically at risk for valve defects.